2015
DOI: 10.12657/folmal.023.005
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial snails (Mollusca: Gastropoda) of the Gyaros Island (Cyclades, Greece)

Abstract: Although most of the Cyclades and other Aegean islands and islets have been surveyed for land snails since the beginning of the 19th century, the island of Gyaros was not one of them. Five species were recorded by two geologists who studied the geology of the island in 1952. In our survey in March 2014 we found 20 species on the island. All species, with the exception of Chilostoma arcadica and Monacha rothii, are widespread in the Aegean and the Mediterranean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Their fauna consists mostly of Mediterranean species (13 of 18 species), which is in agreement with [33]. Other studies [44,45] also report that mollusk assemblages found in cultivated or formerly cultivated areas in the Aegean islands are dominated by Mediterranean species.…”
Section: Discussionsupporting
confidence: 87%
“…Their fauna consists mostly of Mediterranean species (13 of 18 species), which is in agreement with [33]. Other studies [44,45] also report that mollusk assemblages found in cultivated or formerly cultivated areas in the Aegean islands are dominated by Mediterranean species.…”
Section: Discussionsupporting
confidence: 87%
“…We extend our analysis to include Gyaros Island, an uninhabited landmass spanning approximately 21 km 2 , characterized by an arid environment and covered uniformly with numerous shrubs (Vardinoyannis et al., 2015). The slope‐area analysis for the island (see Figure S1b in Supporting Information ) reveals the presence of two dominant regimes of sediment transport, namely a debris‐dominated regime at small spatial scales and the fluvial erosion regime at large spatial scales.…”
Section: Eikonal Landscapesmentioning
confidence: 99%